Ce que les discriminations font aux individus et aux sociétés - François Dubet (Casa de Velázquez, 2017)
Discriminatory practices entail a twofold denial: on the one hand they deny the equality and merit of any individual. And on the other hand they appeal to recognition of the ethnic and/or sexual identities at the root of individual cases of discrimination. These practices require a twofold response: a demand for liberty and a demand for recognition, which no democratic society can reasonably deny. Then again the demand for equality places the focus on social balances and universal conceptions of justice. But above all, the demand for recognition brings into question majority identities, which are no longer seen as the products of «nature» as relating to sexual identities, or of history as relating to national identities. Henceforth majority identities become «minority», singular identities even where they are statistically a majority. Thus logically the struggle against forms of discrimination meets stiff resistance. Indeed, these demands make it essential for societies to regain the capacity to define what is shared in common over and above inequalities and differences.